2013
DOI: 10.1016/j.bbadis.2013.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of tumorigenicity by MicroRNA-138 through inhibition of EZH2-CDK4/6-pRb-E2F1 signal loop in glioblastoma multiforme

Abstract: Deregulation of microRNAs (miRNAs) is implicated in tumor progression. We attempt to identify the tumor suppressive miRNA not only down-regulated in glioblastoma multiforme (GBM) but also potent to inhibit the oncogene EZH2, and then investigate the biological function and pathophysiologic role of the candidate miRNA in GBM. In this study, we show that miRNA-138 is reduced in both GBM clinical specimens and cell lines, and is effective to inhibit EZH2 expression. Moreover, high levels of miR-138 are associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 53 publications
3
63
1
Order By: Relevance
“…In addition, multivariate survival analysis indicated that low expression of miR-138 was an independent prognostic factor for patients with hepatocellular carcinoma (31). In glioblastoma, high expression levels of miR-138 were associated with a long overall and progression-free survival time (32). These findings suggested that miR-138 may represent a promising prognostic biomarker of human cancer.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, multivariate survival analysis indicated that low expression of miR-138 was an independent prognostic factor for patients with hepatocellular carcinoma (31). In glioblastoma, high expression levels of miR-138 were associated with a long overall and progression-free survival time (32). These findings suggested that miR-138 may represent a promising prognostic biomarker of human cancer.…”
Section: Discussionmentioning
confidence: 69%
“…Downregulation of miR-138 has been identified in several cancer types, including breast cancer (21), bladder cancer (22), larynx carcinoma (23), colorectal cancer (24,25), non-small cell lung cancer (26,27), oral squamous cell carcinoma (28), gallbladder carcinoma (29), pancreatic cancer (30), hepatocellular carcinoma (31) and glioblastoma (32). More significantly, miR-138 expression levels were observed to be correlated with clinicopathological features of cancer patients.…”
Section: Discussionmentioning
confidence: 98%
“…miR-138/SP1-based targeted therapy could therefore represent a promising therapeutic strategy for HCC patients. Downregulation of miR-138 has been reported in diverse types of human cancer, including anaplastic thyroid carcinoma (21), head and neck squamous cell carcinoma (22), clear cell renal cell carcinoma (23), ovarian cancer (24), glioblastoma (25), colorectal cancer (26), non-small cell lung cancer (NSCLC) (27), pancreatic cancer (28) and breast cancer (29). Furthermore, reduced miR-138 expression was associated with a number of cancer characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…partial From the therapeutic point of view, EZH 2-mediated signal loop, EZH2-CDK4/6-pRb-E2F1, which is involved in carcinogenesis of glioma, could be inhibited by the candidate miRNA. MiR-138 is the miRNA that is diminished in gB samples and potent to suppress EZH2 expression through inhibition of EZH2-CDK4/6-pRb-E2F1 signal loop (32).…”
Section: Discussionmentioning
confidence: 99%